2018
DOI: 10.1177/0361198118758683
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Gradation of Fine Processed Reclaimed Asphalt Pavement and Aggregate Blends for Unbound Base Courses

Abstract: The purpose of this research was to investigate the effect of changes in grain size distribution to the permanent deformation of two different fine processed reclaimed asphalt pavement (RAP) blended with base course virgin aggregate (VA). Grain size distribution of the RAP-VA blends were created following two different approaches. The first approach was based on mixing RAP and VA to have one grain size distribution, regardless of how much RAP was added to VA (here referred to as the engineered mixture design).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…The VA used in this study was classified as a typical base course material (21 aggregate gradation) by Virginia Department of Transportation (VDOT) as defined by their Road and Bridge Standards ( 32 ). This was the same material used in the previous study conducted by the authors when the performance of the RAP blended with VA was evaluated in the laboratory ( 8 ). The aggregate was created from the crushing of diabase rock and consisted of a maximum particle size of 25.4 mm and 11% fines.…”
Section: Materials Characterizationmentioning
confidence: 99%
See 3 more Smart Citations
“…The VA used in this study was classified as a typical base course material (21 aggregate gradation) by Virginia Department of Transportation (VDOT) as defined by their Road and Bridge Standards ( 32 ). This was the same material used in the previous study conducted by the authors when the performance of the RAP blended with VA was evaluated in the laboratory ( 8 ). The aggregate was created from the crushing of diabase rock and consisted of a maximum particle size of 25.4 mm and 11% fines.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…The RAP used in this study was obtained from two different asphalt plants in Virginia. These were also the same materials that were previously used by the authors as part of the laboratory performance evaluation study ( 8 ). Both of these RAP materials classified as fine processed RAP with maximum particles being less than 12.7 mm sieve size.…”
Section: Materials Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hoppe et al [17] looked into the feasibility of utilizing RAP for road base applications, his review indicated a current direction to incorporate RAP to levels reaching 50% in unbound base layer blends; however, there is a lack of uniformity and limited specifications. Recent research by Ullah et al [18] investigated the impact of alterations in gradation in regards to the permanent deformation effects by looking into a variety of prepared RAP's that was combined together with virgin aggregate for the base course. The research aimed to improve gradation curves and to establish limits for mixtures containing RAP that may result in similar or better performance than the 100% VA that is used to construct base courses.…”
Section: Use Of Rap For Unbound Pavement Layersmentioning
confidence: 99%